The Earth's Worst Climate Disaster - Kopp, Robert E.; Kirschvink, Joseph L. (NHK (Japan Broadcasting Corporation), 2004)
Scientists, environmentalists, and the wiser members of the political class worry today about global climate change. Will rising tides plunge Tokyo, London, and New York beneath the ocean’s waves? Will meltwater pouring off of North America shift the circulation of the North Atlantic Ocean and plunge Europe into an Ice Age? Yet, as worrisome as these prospects are, the Earth has faced far greater climatic catastrophes in the past. The greatest among these was the Paleoproterozoic Snowball Earth event, which 2.3 billion years ago smothered the planet with a blanket of ice for tens of millions of years.